Safety and effectiveness of laparoscopic Y-en-Roux gastric bypass surgery in obese elderly patients - Santos,Marcelo Protásio dos (2020)
Abstract Purpose To analyze, in aged obese patients, the weight loss, comorbidity control, and safety postoperative complications of bariatric surgery by Roux-en-Y gastric bypass technique. Methods Twenty-seven patients who underwent laparoscopic weight-reducing gastroplasty with Roux-en-Y gastric bypass to treat obesity were included. All patients were ≥ 60 years old at the time of surgery. The Wilcoxon test was used for statistical analysis, and a p-value ≤0.05it was considered significant. Results Ten (90.9%) patients with dyslipidemia were cured (p < 0.001). Nine (81.8%) patients with type 2 diabetes mellitus had total improvement and 2 (18.2%) had partial improvement (p = 0.003). In 23 patients with systemic arterial hypertension, 9 (39.1%) achieved total improvement and 14 (60.9%) partial improvement (p = 0.140). Five (71.4%) patients with obstructive sleep apnea syndrome were cured (p = <0.001). For other comorbidities, no partial improvement or cure was shown. Conclusions Roux-en-Y gastric bypass surgery in obese elderly patients can be performed safely and with low morbidity and mortality rates. The benefits of weight loss and reduced comorbidities are promising and like those of the younger population.